Meta-Analysis of Sex Differences in Social and Communication Function in Children With Autism Spectrum Disorder and Attention-Deficit/Hyperactivity Disorder - Mahendiran, Tania; Brian, Jessica; Dupuis, Annie; Muhe, Nadia; Wong, Pui-Ying; Iaboni, Alana; Anagnostou, Evdokia (Frontiers in Psychiatry, 2019)
Background: Sex differences in the prevalence of neurodevelopmental disorders such as autism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD) are well documented, but studies examining sex differences in social and communication function remain limited and inconclusive. Objectives: The objective of this study is to conduct a meta-analysis of sex differences in social-communication function in children with ASD or ADHD and typically developing controls. Methods: Using PRISMA, a search was performed on Medline and PSYCHINFO on English-language journals (2000–2017) examining sex differences in social and communication function in ASD and ADHD compared to controls. Inclusion criteria: 1) peer reviewed journal articles, 2) diagnosis of ASD or ADHD and controls, 3) age 6–18 years, 4) measures of social–communication function, and 5) means, standard deviations, and sample sizes reported in order to calculate standardized mean differences (SMD). Results: Eleven original/empirical studies met inclusion criteria for ASD and six for ADHD. No significant sex differences were found between ASD and controls in social (SMD = −0.43; p = 0.5; CI: −1.58–0.72), or communication function (SMD = 0.86; p = 0.5 CI; −1.57–−3.30) and between ADHD and controls in social function (SMD = −0.68: p = 0.7, CI: −4.17–2.81). No studies evaluated sex differences in communication in ADHD. Significant heterogeneity was noted in all analyses. Type of measure may have partially accounted for some variability between studies. Conclusions: The meta-analysis did not detect sex differences in social and communication function in children with ASD and ADHD; however, significant heterogeneity was noted. Future larger studies, controlling for measure and with adequate numbers of female participants are required to further understand sex differences in these domains.